2001
DOI: 10.1210/jcem.86.3.7296
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the Nocturnal Testosterone Rhythm by Sleep Fragmentation in Normal Men

Abstract: Recently, we have demonstrated that in normal men the nocturnal testosterone rise antedated the first rapid eye movement (REM) sleep episode by about 90 min and was correlated with REM latency. To further elucidate whether the diurnal testosterone rhythm is a sleep-related phenomenon or controlled by the circadian clock, we determined serum testosterone levels in 10 men during the ultrashort 7/13 sleep-wake cycle paradigm. Using this schedule, subjects experienced partial sleep deprivation and fragmented sleep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
82
2
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(88 citation statements)
references
References 13 publications
2
82
2
2
Order By: Relevance
“…Administration of testosterone to obese men improves insulin sensitivity (26), and, conversely, insulin is also thought to regulate testosterone (27). Previous studies have also linked sleep disruption with reduced testosterone levels (28).…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…Administration of testosterone to obese men improves insulin sensitivity (26), and, conversely, insulin is also thought to regulate testosterone (27). Previous studies have also linked sleep disruption with reduced testosterone levels (28).…”
Section: Biological Mechanismsmentioning
confidence: 99%
“…Testosterone secretion is tightly linked to sleep cycles, with peak levels occurring just before or after REMS onset [66]. Insufficient and/or fragmented sleep blocks the nocturnal increase in testosterone [67][68][69]. Yet, findings that fluctuations in testosterone levels affect sleep in men remain inconsistent.…”
Section: (C) Sex Steroids Influence Sleepmentioning
confidence: 99%
“…32,33,40 These studies also revealed a significant correlation between maximal testosterone levels and total oxygen desaturation time. 32,33 In our study, this correlation was significant for both oxygen desaturation variables, ODI and O 2 nadir. The relationship between the reduction in TT and elevated ODI persisted even after adjusting for BMI.…”
Section: Discussionmentioning
confidence: 64%
“…14,25,30 The significant association of low TT levels with high AHI values suggest that gonadal dysfunction is a consequence of OSA rather than a primary condition independent of the hypothalamic-pituitarygonadal axis. 4,32,33 Several factors may account for lower testosterone secretion levels in middle-aged men with OSA, including hypoxemia, 14,29 fragmented sleep, obesity, 21,34 and advanced age. 2 There has been growing recognition that sex hormones play important roles in almost all physiological processes, including breathing.…”
Section: Discussionmentioning
confidence: 99%